Mixed valence trinuclear cobalt (II/III) complexes: Synthesis, structural characterization and phenoxazinone synthase activity. (25th September 2017) - Hazari, Alokesh; Das, Avijit; Mahapatra, Prithwish; Ghosh, Ashutosh
Graphical abstract: Two of the three complexes are the first examples of the terminal coordination of carboxylato ion to Co(III) of a mixed valence Co III Co II Co III complex with 1, 3-propanediammine based Schiff base ligand and one shows phenoxazinone synthase activity with considerably high turnover number. Abstract: Three new mixed valence trinuclear Co(II/III) compounds [Co3 L2 ( μ 2 -C6 H5 CO2 − )2 (CH3 CN)2 ](ClO4 − )2 ·(CH3 CN)3 (1 ) [Co3 L R 2 ( μ 2 -C6 H5 CO2 − )2 (C6 H5 CO2 − )2 ]·(CH3 CN)2 (2 ) and [Co3 L R 2 ( μ 2 -C6 H5 CHCHCO2 − )2 (C6 H5 CHCHCO2 − )2 ]·((CH3 )2 CO)2 (3 ) have been synthesized by reacting the di-Schiff base ligand [H2 L] or its reduced analog [H2 L R ] (where H2 L = N, N ′-bis(salicylidene)-1, 3-propanediamine) and (H2 L R = N, N ′-bis(2-hydroxybenzyl)-1, 3-propanediamine) with cobalt perchlorate hexahydrate and sodium benzoate or sodium cinnamate. The complexes have been characterized by IR, UV–Vis and single crystal X-ray diffraction analyses. All the complexes are linear trinuclear species [Co III Co II Co III ] in which two terminal octahedral Co III N2 O2 cores coordinate to the central octahedral Co II ion through μ2 -phenoxido oxygen atom and the bridging carboxylato ions. In addition, the complexes (2 and3 ) derived from reduced Schiff base ligand have, rather unusually, a terminally coordinated carboxylato ion to Co III, which is acetonitrile molecule in case of complex (1 ) with unreduced ligand. Complex2 has been found to be an excellent functional model for the phenoxazinone synthase activity, in the aerial oxidation of 2-aminophenol to the corresponding 2-aminophenoxazine-3-one chromophore in acetonitrile solvent medium. Detailed kinetic data analysis of this oxidation reaction reveals a fairly high phenoxazinone synthase activity of2 with k cat = 153.60 h −1 .